Lithium Salt Association-Mediated Interfacial Charge Exchange for Low-Temperature Lithium-Metal Batteries: Beyond Lithium De-Solvation Manner - Fei Zhao; Jin-Hao Zhang; Jin-Xiu Chen; Zhi-Yuan Gu; Xiao-Zhong Fan; Lin Zhu; Hui-Ling Na; Ming-Xia Dong; Cao Guan; Long Kong (Research)
Fairly assessing energy barrier that shifts coordinated lithium (Li) to naked Li on the interface, as well as deeply exploring interfacial descriptors that can interpret rapid interfacial redox kinetics with anion-dominated electrolyte species, has been long-standing fundamentals to design well-performing electrolytes for low-temperature Li metal batteries. The Li de-solvation concept is merely a picture that can describe the transformation of coordinated Li to naked Li. This work highlights the importance of Li de-coordination instead of Li de-solvation to illustrate such Li transformation behavior, since it considers entire Li de-sheath events (both solvent and anion). Theoretical calculations inform that anions entering into the first Li solvation sheath (mimic to the weak solvation electrolyte) unavoidably elevate the Li de-coordination energy due to the intrinsically greater ion–ion than ion–dipole interactions in the bulk electrolyte. The subsequent interfacial model suggests that interfacial charge exchange is a more effective descriptor to mediate interfacial redox kinetics and interpret experimental results that anion-rich Li species exhibit better battery performances. This work underscores anion effects on the Li de-coordination in the bulk electrolyte and charge exchange in the interface, hoping to unveil the fundamental causes why anion-prevailed Li species work well in low-temperature Li metal batteries.